A case study of homeless women living on the streets of Braamfontein, Johannesburg - Msimango, Thando Dimakatso (University of the Witwatersrand, Johannesburg, 2023)
Homelessness is a global concern. Several factors that trigger homelessness, such as natural disasters and wars, poor education, poverty, substance abuse, domestic violence and mental illness, have frequently been identified. South Africa has seen an increase in the number of people living on the streets of its major cities. This has culminated in the initiation of different research studies looking into the phenomenon of homelessness. However, there seems to be a gap in the studies looking at the plight of homeless women within the Braamfontein area of Johannesburg. Therefore, this study explored the experiences of homeless women living on the streets of Braamfontein and is based on a constructivist paradigm. The study adopted a qualitative approach, and a single case study design was adopted. Snowball sampling was used to select 13 participants who met the selection criteria. A semi-structured interview guide was used as a research tool, and one-on-one-in-depth interviews were used to collect data. Thematic analysis was also used to analyse the data. The study can contribute to developing and enhancing gender-specific intervention programmes earmarked for women living on the streets of Braamfontein in Johannesburg. It is hoped that the study might also initiate debates around the subject matter. Recommendations are made for future research.
A research report submitted in partial fulfilment of the degree of Mater of Arts in Social Development to the Faculty of Humanities, Department of Social Work, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Homelessness; Homeless women; Social Development; Intersectionality; UCTD